Moving the field of vocabulary assessment forward: The need for more rigorous test development and validation. (January 2020) - Schmitt, Norbert; Nation, Paul; Kremmel, Benjamin
Abstract: Recently, a large number of vocabulary tests have been made available to language teachers, testers, and researchers. Unfortunately, most of them have been launched with inadequate validation evidence. The field of language testing has become increasingly more rigorous in the area of test validation, but developers of vocabulary tests have generally not given validation sufficient attention in the past. This paper argues for more rigorous and systematic procedures for test development, starting from a more precise specification of the test's purpose, intended testees and educational context, the particular aspects of vocabulary knowledge which are being measured, and the way in which the test scores should be interpreted. It also calls for greater assessment literacy among vocabulary test developers, and greater support for the end users of the tests, for instance, with the provision of detailed users' manuals. Overall, the authors present what they feel are the minimum requirements for vocabulary test development and validation. They argue that the field should self-police itself more rigorously to ensure that these requirements are met or exceeded, and made explicit for those using vocabulary tests.